The Influence of Leadership Style, Communication, and Work Discipline on Employee Performance of PT Sinar Gunung Sawit Raya - Purnama Yanti Purba; Ricky Van Houten; Nadessah Riama Sello Siahaan; Marco Yeremia Nababan; Dolly Christian Sinaga (International Journal of Social Science and Business, 2022)
Amid the Covid-19 pandemic, economic growth in various business sectors worldwide has decreased. The background of this research is the phenomenon of not achieving production targets, leaders who are too strict with subordinates, communication between employees is not good, and lack of discipline and self-awareness of employees in carrying out regulations. This study aimed to examine and analyze the effect of Leadership Style, Communication, and Work Discipline on Employee Performance at PT Sinar Gunung Sawit Raya. The approach in this study is a quantitative descriptive approach. The population totals 140 employees. The technique of determining the sample is simple random sampling. Collecting data in this study using observation, questionnaires, and documentation studies. The data analysis method used is multiple linear regression. Partial test results Leadership style has a positive and significant effect on employee performance. Communication has a positive and significant effect on employee performance, and work discipline has a positive and significant effect on employee performance at PT Sinar Gunung Sawit Raya. Simultaneously Leadership Style, Communication, and Work Discipline positively and significantly affect Employee Performance at PT. Rays of Gunung Sawit Raya.